(untitled) (Bangladesh Journal of Botany, 2013)
A methanolextract of the leaves of Parabaena sagitatta Miers and its petroleum ether, carbon tetrachloride, dichloromethane, ethylacetate and aqueous soluble partitionates were evaluated for antioxidant activity by 1,1-diphenyl-2-picrylhydrazyl (DPPH), Folin-Ciocalteau reagent and phosphomolybdenum total antioxidant assays by using butylated hydroxytolune (BHT) and ascorbic acid as standards. The dichloromethane soluble fraction demonstrated the presence of significant amount of phenolic compounds 61.06 ± 0.54 mg GAE/g of extract and also has moderate antioxidant activity IC50 50.62 ± 0.25 ?g/ml. A positive correlation (R2), 0.969 was observed between total phenolic content and total antioxidant activity of P. sagitatta. The general toxicity was determined by brine shrimp lethality bioassay where the dichloromethane LC50 DOI: http://dx.doi.org/10.3329/bjb.v41i2.13441 Bangladesh J. Bot. 41(2): 155-158, 2012 (December)